2018
DOI: 10.1123/jsm.2017-0268
|View full text |Cite
|
Sign up to set email alerts
|

Disrupting the Disruptor: Perceptions as Institutional Maintenance Work at the 1968 Olympic Games

Abstract: How people reflect on and discuss protests at sporting events is a relevant question of interest to sport management scholars. This article uses qualitative data to understand how institutional members reflect on and discuss a disruptive act that violates institutional rules and norms. The authors study the historical case of Tommie Smith and John Carlos’ silent protest at the 1968 Olympic Games in Mexico City. Relying on interview data from Smith and Carlos’ teammates (59) on the 1968 U.S. Olympic Team, the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 52 publications
2
28
0
2
Order By: Relevance
“…Sport management scholars have supported mainstream findings showing that institutional maintenance work is resultant from threats to dominant sport institutions (see Micelotta & Washington, 2013). Agyemang et al (2018) provided a micro-level account of institutional maintenance with their study of Tommie Smith and John Carlos' protests at the 1968 Olympics. They found that actors with different interests, framed by different institutional logics, encountered threats to dominant institutional norms.…”
Section: Institutional Maintenance Workmentioning
confidence: 94%
See 1 more Smart Citation
“…Sport management scholars have supported mainstream findings showing that institutional maintenance work is resultant from threats to dominant sport institutions (see Micelotta & Washington, 2013). Agyemang et al (2018) provided a micro-level account of institutional maintenance with their study of Tommie Smith and John Carlos' protests at the 1968 Olympics. They found that actors with different interests, framed by different institutional logics, encountered threats to dominant institutional norms.…”
Section: Institutional Maintenance Workmentioning
confidence: 94%
“…However, few have provided specific accounts of actors engaging in institutional disruption work. Agyemang et al (2018) documented how the protests of Tommie Smith and John Carlos at the 1968 Olympics were a form of institutional disruption. Nite and Hagan (2017) examined the media discourse of how institutional disruption may occur when institutional leaders alienate subordinates and enact values that are counter to those of subordinates and some fans.…”
Section: Institutional Disruption Workmentioning
confidence: 99%
“…Additionally, a case study provides an effective research design to understand the complexities of a given phenomenon and can lead to novel and intriguing findings (Eisenhardt, 1989). Though case studies have limited generalizability, scholars and practitioners can develop a greater understanding of participants' experiences from case studieswhich can then assist in theory development and explication (Agyemang, Berg, & Fuller, 2018;Stebbins, 2006).…”
Section: Methods Research Designmentioning
confidence: 99%
“…For those unfamiliar with the work of Edwards, he is one of the founders of the Olympic Project for Human Rights (OPHR), which he used as an organizational platform to help organize the US athletes’ protests during the height of the civil rights era. He is arguably most well-known for helping spark the US Olympic sprinters, John Carlos’ and Tommie Smith’s black gloved fist protest (against racism and economic injustice in the United States) on the victory stand during the playing of the US national anthem at the 1968 Olympic Games in Mexico City (Agyemang et al, 2018).…”
Section: Organizations and Activismmentioning
confidence: 99%